Rancang Bangun Model Blended Learning Interaktif Berbasis LMS untuk Pembelajaran Teknik - Effendi, Hansi; Nanda, Is Prima (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Learning in the field of Engineering has unique characteristics that differentiate it from general education, particularly in the need to integrate theory with practice, solve project-based problems, and utilize technology to support simulations and experiments. With the advancement of digital learning technologies, Learning Management System (LMS)-based blended learning emerges as a promising approach to facilitate more interactive and flexible learning processes in Engineering education. However, blended learning models specifically designed to address the unique needs of engineering education remain limited. This study aims to design an interactive blended learning model based on LMS tailored to the characteristics of Engineering education. The model was developed using the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation), with an emphasis on utilizing LMS features such as interactive modules, technical simulations, discussion forums, formative assessments, and project-based tasks. The model underwent validation by experts in engineering education and instructional technology to assess its relevance, practicality, and strengths. The findings reveal that the proposed blended learning model effectively meets the needs of Engineering education by integrating theory and practice in a digital environment. Expert validation yielded high scores for relevance and practicality, highlighting the model’s strengths in fostering interactivity while suggesting areas for further improvement. This article contributes by offering a technical guide for designing LMS-based blended learning models, serving as a foundation for more innovative and adaptive engineering education development in the future.